2022
DOI: 10.1371/journal.pgph.0001215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with anogenital warts among sexual and gender minorities attending a trusted community health center in Lagos, Nigeria

Abstract: Anogenital warts caused by human papillomavirus are common in sexual and gender minorities (SGM). The prevalence of, and factors associated with warts were described for SGM with a high burden of HIV in Nigeria. Individuals who reported anal sex with men were enrolled in the TRUST/RV368 cohort. Participants completed an interviewer-led survey, provided biological samples, and had a physical examination. Specific to the Lagos site, clinic staff offered standardized warts treatment services. RDS-weighted multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…HPW who are single were more likely to have AGWs compared to those who were married. This observation aligns with the results reported in certain studies, yet it contradicts the findings reported in another study [ 9 , 14 ]. This phenomenon can likely be attributed to the increased vulnerability of unmarried women to engaging in risky sexual behaviors, such as having multiple sexual partners, engaging with partners who have multiple sexual partners, and having a high number of sexual partners [ 23 - 25 ], which are risk factors for AGW.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…HPW who are single were more likely to have AGWs compared to those who were married. This observation aligns with the results reported in certain studies, yet it contradicts the findings reported in another study [ 9 , 14 ]. This phenomenon can likely be attributed to the increased vulnerability of unmarried women to engaging in risky sexual behaviors, such as having multiple sexual partners, engaging with partners who have multiple sexual partners, and having a high number of sexual partners [ 23 - 25 ], which are risk factors for AGW.…”
Section: Discussionsupporting
confidence: 87%
“…According to the available data, individuals with higher levels of education or occupations in professional fields tend to exhibit a reduced likelihood of experiencing AGW [21]. However, it is essential to note that these findings contradict the results of another study, where education and occupation did not impact the risk of developing AGW [14].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…It has become common knowledge that receptive anal sex is associated with many sexually transmitted infections, including HPV. 44,45 Many of the participants may have experienced rectal gonorrhea, chlamydia, and HPV-associated anal warts 46,47 ; all associated with increased anal symptoms that require medical attention. It may be that knowing an additional medical condition, such as anal cancer, heightens levels of worry.…”
Section: Discussionmentioning
confidence: 99%